From lilac to larkspur: self-refutation in T. S. Eliot’s later poetry - Joyce, Chris (Revista Leitura, 2019)
This paper argues that much of Eliot's poetry is unconsciously self-refutational and self-deceived. Our attention is distracted from this by its lyricism and intensely personal poignancy. Disgust at the contemplation of humanity, and self-disgust, underlie Eliot's parodie treatment of life: the horror of the sinfulness of the flesh, which can 'only die'. I argue that, while we cannot ask a poet to give an untruthful report of experience, something is wrong when the creative faculty is given so strongly to expressions of general disgust, over and above Eliot's anti-semitism, misogyny, sexual ambivalence and prurience. To counterbalance this effect, Eliot posits tlie ambivalent 'enchantment' of 'death's twilight kingdom', with its promise of redemption from sin, and the enchantment of childhood memories, which he presents as ultimately beguiling and illusory. But in 'Marina' the quasi-liturgical passage on spiritual death is 'placed' by the effect of the poem as a whole. Similarly, the life and vitality of the sixth section of 'Ash-Wednesday' evokes poetic values which repudiate the author's conscious intentions. In 'Little Gidding' he recalls 'Things ill done and done to others' harm.' It is the compound ghost who speaks (containing the Eliotic alter-ego), the Brunetto Latini of Canto XV of the Inferno. That Eliot is, in a broad sense, sexually — and therefore humanly — maladjusted explains the persistent presence in his work of a condition which 'remains to poison life and obstruct action.' His major critics have been curiously uncritical in this regard. His exasperation I suggest, is not with the deceptions of humanism but, part-unconsciously, with the self-deceived character of his Christian 'acceptance'. This is poetry of self-appeasement. DOI: 10.28998/0103-6858.2005v2n36p71-83